2022
DOI: 10.1136/archdischild-2021-323441
|View full text |Cite
|
Sign up to set email alerts
|

Social communication skill attainment in babies born during the COVID-19 pandemic: a birth cohort study

Abstract: IntroductionThe SARS-CoV-2 (COVID-19) pandemic was managed with sustained mass lockdowns to prevent spread of COVID-19 infection. Babies born during the early stages of the pandemic missed the opportunity of meeting a normal social circle of people outside the family home.MethodsWe compared 10 parentally reported developmental milestones at 12-month assessment in a cohort of 309 babies born at the onset of the pandemic (CORAL cohort) and 1629 babies from a historical birth cohort (BASELINE cohort recruited bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 17 publications
(41 reference statements)
6
22
0
Order By: Relevance
“…The ongoing prospective COVID-19 Mother Baby Outcomes (COMBO) Initiative previously reported no neurodevelopmental differences at age 6 months in infants with and without exposure to maternal SARS-CoV-2 infection during pregnancy on any of the 5 subdomains of the parent-reported Ages & Stages Questionnaires, third edition (ASQ-3), in a cohort from New York City. Similar null results on the ASQ-3 among infants with prenatal exposure to maternal SARS-CoV-2 infection have been reported from other geographical regions, including Kuwait and China; however, it should be noted that both the COMBO Initiative and other research groups have found slightly lower parent-reported developmental scores in infants born during the pandemic compared with those born before the pandemic. To date, the cumulative available data have relied on parent-reported measures such as the ASQ-3, which has only moderate sensitivity and specificity for estimating actual neurodevelopmental delays .…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The ongoing prospective COVID-19 Mother Baby Outcomes (COMBO) Initiative previously reported no neurodevelopmental differences at age 6 months in infants with and without exposure to maternal SARS-CoV-2 infection during pregnancy on any of the 5 subdomains of the parent-reported Ages & Stages Questionnaires, third edition (ASQ-3), in a cohort from New York City. Similar null results on the ASQ-3 among infants with prenatal exposure to maternal SARS-CoV-2 infection have been reported from other geographical regions, including Kuwait and China; however, it should be noted that both the COMBO Initiative and other research groups have found slightly lower parent-reported developmental scores in infants born during the pandemic compared with those born before the pandemic. To date, the cumulative available data have relied on parent-reported measures such as the ASQ-3, which has only moderate sensitivity and specificity for estimating actual neurodevelopmental delays .…”
Section: Introductionsupporting
confidence: 75%
“…This study addressed several limitations of previous studies by the COMBO initiative 16 and other research groups. 19 , 20 Previous work by the COMBO Initiative 16 was limited to infants born in New York City during the initial wave of the COVID-19 pandemic, while the current analysis included infants born across 3 distinct geographic regions in the US. The previous study 16 also relied on a parental report measure and was therefore subject to potential parental biases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of infants who have lived some portion of their life during the pandemic have demonstrated deficits in communication, motor and personal/social scores 7–9. We have previously demonstrated that an Irish birth cohort born into the pandemic had reduced social communication skills relative to a historic Irish cohort at 12 months of age 10. This has been confirmed in a recent systematic review looking at developmental outcomes 11.…”
Section: Introductionsupporting
confidence: 58%
“…For example, parents were socially isolated during lockdown ( 7 ) and, thus, did not receive professional and experienced parenting guidance on time ( 26 ), which has caused changes in family behaviors ( 27 ). A study also stated that social isolation leaves infants with potential deficits in social communication skills ( 28 ). Okinarum and Rochdia noted that the weakened breastfeeding experience during the COVID-19 pandemic was dominated by impaired comfort, inadequate milk supply, parenting problems, and indifferent spouses ( 29 ).…”
Section: Introductionmentioning
confidence: 99%